Maternal Exposure to Ethanol During Pregnancy and Lactation Affects Glutamatergic System and Induces Oxidative Stress in Offspring Hippocampus. (January 2016) - Cesconetto, Patricia A.; Andrade, Camila M.; Cattani, Daiane; Domingues, Juliana T.; Parisotto, Eduardo B.; Filho, Danilo W.; Zamoner, Ariane
Abstract : Background: Alcohol abuse during pregnancy leads to intellectual disability and morphological defects in the offspring. The aim of this study was to determine the effect of chronic maternal ethanol (EtOH) consumption during pregnancy and lactation on glutamatergic transmission regulation, energy deficit, and oxidative stress in the hippocampus of the offspring. Methods: EtOH was administered to dams in drinking water at increasing doses (2 to 20%) from the gestation day 5 to lactation day 21. EtOH and tap water intake by treated and control groups, respectively, were measured daily. Results: Results showed that EtOH exposure does not affect fluid intake over the course of pregnancy and lactation. The toxicity of maternal exposure to EtOH was demonstrated by decreased offspring body weight at experimental age, on postnatal day 21. Moreover, maternal EtOH exposure decreased 45 Ca 2+ influx in the offspring's hippocampus. Corroborating this finding, EtOH increased both Na + ‐dependent and Na + ‐independent glial [ 14 C]‐glutamate uptake in hippocampus of immature rats. Also, maternal EtOH exposure decreased glutamine synthetase activity and induced aspartate aminotransferase enzymatic activity, suggesting that in EtOH‐exposed offspring hippocampus, glutamate is preferentially used as a fuel in tricarboxylic acid cycle instead of being converted into glutamine. In addition, EtOH exposure decreased [U‐14C]‐2‐deoxy‐D‐glucose uptake in offspring hippocampus. Conclusions: The decline in glucose transport coincided with increased lactate dehydrogenase activity, suggesting an adaptative response in EtOH‐exposed offspring hippocampus, using lactate as an alternative fuel. These events were associated with oxidative damage, as demonstrated by changes in the enzymatic antioxidant defense system and lipid peroxidation. Taken together, the results demonstrate that maternal exposure to EtOH during pregnancy and lactation impairs glutamatergic transmission, as well as inducing oxidative stress and energy deficit in immature rat hippocampus.